Pengaruh Pajak Reklame dan Pajak Restoran Terhadap Pendapatan Asli Daerah di Kota Surabaya - Mahmud Nur Virgian Syah; Nurul Hanifa (Jurnal Ekonomika : INDEPENDEN, 2022)
The aim of this article is to identify the effect of the advertisement tax and restaurant tax on Regional Original Income of Surabaya in 2011 – 2018. By using quantitative descriptive with multiple linear analysis and secondary data which were in the form of time series for the period 2011-2018, the data processing was assisted by a software named SPSS 25. The test results show that 1). The advertisement tax partially does not affect the Regional Original Income. 2). Restaurant tax affects Regional Original Income. 3). Advertising and restaurant taxes affect Regional Original Income. Keywords: Tax, Advertising, Restaurant